Novel hepatitis B virus strain developing due to recombination between genotypes H and B strains isolated from a Japanese patient. Issue 11 (25th October 2013) - Uchida, Yoshihito; Kouyama, Jun‐ichi; Naiki, Kayoko; Sugawara, Kayoko; Inao, Mie; Nakayama, Nobuaki; Mochida, Satoshi
<x xml:space="preserve">Abstract</x> Aim In Japan, genotypes B and C are the predominant genotypes isolated from patients with chronic hepatitis B, while genotype A predominates in patients with acute hepatitis B. Globalization, however, appears to have changed the distribution of the hepatitis B virus (HBV) genotypes. Thus, the viral characteristics of HBV genotypes other than genotypes A, B and C were examined. Methods Screening of genotypes was performed by enzyme immunoassay and/or polymerase chain reaction INVADER method in 222 patients with HBV. The full‐length nucleotide sequences of unusual strains were compared to those in the database, followed by construction of a phylogenetic tree. Results Unusual HBV strains were isolated from two patients: a 27‐year‐old Japanese bisexual man with acute hepatitis B with HIV co‐infection and a 52‐year‐old Japanese man with chronic hepatitis B. The former strain was classified as genotype H, showing an overall identity of 99.8% to the Thailand strain (EU498228), while the nucleotide sequence of the latter strain showed similarity to the genotype B strains isolated in Malaysia (JQ027316) and Indonesia (JQ429079) between DR2 and DR1 in the X region, with identities of 96.9%. However, this strain was classified as genotype H by full‐length sequence analysis, and the sequence between nt2023 and nt2262 showed no similarity to that in any previously reported strains. Conclusion HBV strains showing recombination between genotype B and H strains were found even in chronic hepatitis patients in Japan. Globalization may yield HBV strains of possible novel genotypes containing novel nucleotide sequences in the precore/core region.